Obtaining Butyl Acetate by the Method of Hydrolysis - Nazirova Rakhnamokhon Mukhtarovna; Mirsalimova Saodat Rakhmatjanovna; Isakov Burhon Shuhratjon ogli (International Journal on Orange Technologies, 2021)
Butyl acetate (butyl ether of acetic acid) is the most common solvent in the production and use of paints and varnishes. Dissolves cellulose ethers, oils, fats, chlorinated rubbers, vinyl polymers, carbiol resins, etc. The addition of butyl acetate together with a small amount of butyl alcohol prevents whitening of the lacquer films. It is a fragrant substance that is part of fruit essences and perfume compositions. It is used in the tanning industry as a tannin. It is widely used in the pharmaceutical industry for the separation of primary substances in the production of antibiotics, etc